Entrepreneurial Marketing in the Digital Ecosystem : The Influence of E-commerce Platforms on the Growth of MSMEs in the Post-Pandemic Era - Nanik Wahyuningtiyas; Sudarmiatin Sudarmiatin (International Forum of Researchers and Lecturers, 2025)
This study examines the influence of e-commerce platforms on the growth of MSMEs in the post-pandemic era, focusing on the implementation of entrepreneurial marketing strategies in the digital ecosystem. This research aims to understand how e-commerce platforms help MSMEs in developing more adaptive and effective marketing strategies amid changes in consumer behavior post-pandemic. The method used is a quantitative approach with Structural Equation Modeling (SEM) to analyze the direct and indirect relationship between the use of e-commerce platforms, entrepreneurial marketing strategies, and the growth of MSMEs. The main findings show that the use of e-commerce platforms has a significant effect on entrepreneurial marketing strategies, which in turn encourages the growth of MSMEs. This research contributes to the literature on MSME digitalization, particularly in the context of post-pandemic recovery, and shows how e-commerce platforms can be an important enabler for MSMEs to survive and thrive amid changing market challenges. The urgency of this research lies in its contribution in providing insights into the implementation of innovative digital marketing strategies, which is highly relevant for MSMEs trying to adapt to the post-pandemic business landscape. Keywords: ,